2023
DOI: 10.3390/antiox12050999
|View full text |Cite
|
Sign up to set email alerts
|

Epimedium Aqueous Extract Ameliorates Cerebral Ischemia/Reperfusion Injury through Inhibiting ROS/NLRP3-Mediated Pyroptosis

Abstract: Cerebral ischemia/reperfusion causes exacerbated neuronal damage involving excessive neuroinflammation and oxidative stress. ROS is considered a signal molecule to activate NLRP3; thus, the ROS/NLRP3/pyroptosis axis plays a vital role in the pathogenesis of cerebral ischemia/reperfusion injury (CIRI). Therefore, targeting the inhibition of the ROS/NLRP3/pyroptosis axis may be a promising therapeutic tactic for CIRI. Epimedium (EP) contains many active ingredients (ICA, ICS II, and ICT), which have a wide range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Prior studies have demonstrated the efficacy of Epimedium brevicornu Maxim. along with its primary active metabolites ICS II and ICA, in combating a range of diseases owing to their potent antiinflammatory and antioxidant attributes (Liu et al, 2020;Wu et al, 2023). Consequently, the pharmacological profile of XLGB has motivated further investigation into its therapeutic potential for MI and its associated molecular targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have demonstrated the efficacy of Epimedium brevicornu Maxim. along with its primary active metabolites ICS II and ICA, in combating a range of diseases owing to their potent antiinflammatory and antioxidant attributes (Liu et al, 2020;Wu et al, 2023). Consequently, the pharmacological profile of XLGB has motivated further investigation into its therapeutic potential for MI and its associated molecular targets.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue assessment was carried out using the BCA protein assay as described in our previous study (Wu et al, 2023). Subsequently, the lysates were normalized to equal amounts per group, and 10 μg of protein from the tissue lysates were separated using 12% sodium dodecyl sulfate-polyacrylamide gel electrophoresis.…”
Section: Western Blotmentioning
confidence: 99%